Economic improvement by Processing Tomato into Dried Tomato in Giripurno Village, Batu City - Jariyah; Lilik Suprianti; Endang Pudji W; Reda Rizal (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Tomato is one of the potential agricultural products in Giripurno village, Batu City. Tomato has a delicious taste and good nutrition for health. The production of tomatoes in Batu city reach 11.750 ton in a year. However, the price of tomatoes fluctuates depending on the season. The farmers who are the tomato producers are at risk of being lost. Therefore, innovation is necessary to produce tomatoes to become one long-lasting product that can increase its value. This community service program is intended to increase the value of tomatoes by producing sweet-dried tomatoes in Giripurno Village, Batu city. The program started with an introduction to the Giripurno authorization, surveyed the potential local product, discussed with the local people, solved the problem, socialized the program to the people, trained the local people, and evaluated the program. We also granted the Giripurno authorization for one food dehydrator machine to be used by local people interested in the sweet-dried tomato business. Our program has been done for six months with the result there is an improvement in people's knowledge regarding the usage of tomatoes, the product derived from tomatoes, the way to produce sweet-dried tomatoes, and the business prospect of sweet-dried tomatoes. People also know using an appropriate technology food dehydrator to improve the sweet-dried tomato product.